INFLAMMASOME ACTIVATION AND EVASION BY BACTERIAL PATHOGENS - Ta, Atri (Curr Opin Immunol, 2020)
Innate immune system plays an essential role in combating infectious diseases by recognizing invading pathogens and activating host defense response. Inflammasomes complexes are a central component of the cytosolic innate immune surveillance and are vital in host defense against bacterial pathogens. Bacterial products or pathogen-induced modifications in the intracellular environment are sensed by the inflammasome receptors that form complexes that serve as a platform for caspase-1- or caspase-11-dependent induction of pyroptosis and secretion of cytokines, IL-1β and IL-18. However, several pathogenic bacteria have developed strategies to evade inflammasome activation. This review highlights the recent advances in the mechanism of inflammasome activation by bacterial pathogens and some of the bacterial evasion strategies of inflammasome activation.